BEYOND THE FEAR OF MATH: UNDERSTANDING MATHEMATICS ANXIETY IN HIGHER EDUCATION ACROSS ASIA - Putra, Rahman Pranovri; Ramadhanti, Auliya (International Journal of Multidisciplinary Reseach, 2025)
Mathematics anxiety is one of the major challenges faced by students in higher education in Asia, especially in education systems that emphasize high academic achievement. This problem can negatively impact students' conceptual understanding, motivation to learn, and career choices. This study aims to identify factors that contribute to mathematics anxiety in higher education in Asia and explore strategies that can be applied to overcome it. The method used in this study is a literature study with a descriptive analysis approach. Data were obtained from national and international journals published between 2018 and 2024, focusing on mathematics anxiety among Asian students. The results showed that mathematics anxiety is influenced by various factors, including academic pressure, social expectations, less interactive teaching methods, and negative experiences in previous learning. In addition, there are gender differences in the level of mathematics anxiety, where female students tend to be more susceptible to it. The discussion reveals that effective interventions include cognitive-behavioral therapy, self-efficacy enhancement, social support, and innovations in teaching methods such as problem-solving approaches and the use of technology. By understanding the causal factors and effective mitigation strategies, educational institutions can create a more conducive learning environment for students in facing academic challenges in mathematics.